Formation and Training of Covid-19 Cadres in The Kuin Riverbanks, Banjarmasin City - Farida Heriyani; Lia Yulia Budiarti (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
Covid-19 cases in Indonesia continue to grow rapidly. South Kalimantan (Kalsel) reported the first case of Covid-19 on March 22, 2020, which was a resident of Banjarmasin City, especially North Kuin Village. From this first case, cases in this area continued to increase and local transmissions were found to other residents. This is due to several things, such as the density of the population which is classified as very dense, making it easier for transmission from one patient to another. In addition, the behavior of the community does not pay attention to health protocols with a relatively low socio-economic background, low levels of education and habits that exist in the community such as like to gather and not maintain distance. This activity aims to form and train young people on the banks of the Kuin River as covid-19 cadres who are expected to be examples and an extension of the government to be able to remind themselves, their family, friends and people around them to always apply health protocols to avoid covid-19. This activity is in the form of cadres recruited from young people in the region to be trained and given motivation about health protocols in the era of the Covid-19 pandemic. The training is conducted online. The results of the activity were that 25 youths / girls who became covid-19 cadres were trained and motivated to carry out their duties and functions as covid-19 cadres.